Implementation of Lamport Digital Signature Scheme in Station-to-station Protocol / Nur Ainaa Mat Abu ... [et al.] - Mat Abu, Nur Ainaa; Mohamad Sarif, Siti Nurfazliana; Mohammad Zuki, Intan Nur Athirah; Udin, Md Nizam (UiTM Cawangan Negeri Sembilan, 2021)
Cryptography is a method that guarantees the authenticity and integrity of a message between the communication parties. There are two types of cryptography, private key, and public key cryptography. In public key cryptography, a pair of keys will be used, public key to encrypt the message and private key to decrypt the message. In the cryptography process, it involved the key exchange protocol in which both parties will exchange their keys for the encryption and decryption process. One of the methods to securely exchange the keys is Diffie-Hellman Key Exchange (DHKE) protocol. DHKE allows both parties to safely exchange their keys over the insecure public channel (Paar & Pelzl, 2010). However, DHKE protocol has a problem in the algorithm part where it does not provide the authentication for the message, and this will make it easily exposed to third party interruption like Man-in-the-Middle (MitM) attack (Nan Li, 2010). Thus, in this paper propose the new algorithm in Station to Station (STS) protocol by implementing Lamport digital signature to provide the authentication in DHKE protocol.